SLE: Novel Postulates for Therapeutic Options - Hosszu, Kinga K.; Valentino, Alisa; Peerschke, Ellinor I.; Ghebrehiwet, Berhane (Frontiers in Immunology, 2020)
Genetic deficiency in C1q is a strong susceptibility factor for systemic lupus erythematosus (SLE). There are two major hypotheses that potentially explain the role of C1q in SLE. The first postulates that C1q deficiency abrogates apoptotic cell clearance, leading to persistently high loads of potentially immunogenic self-antigens that trigger autoimmune responses. While C1q undoubtedly plays an important role in apoptotic clearance, an essential biological process such as removal of self- waste is so critical for host survival that multiple ligand-receptor combinations do fortunately exist to ensure that proper disposal of apoptotic debris is accomplished even in the absence of C1q. The second hypothesis is based on the observation that locally synthesized C1q plays a critical role in regulating the earliest stages of monocyte to dendritic cell (DC) differentiation and function. Indeed, circulating C1q has been shown to keep monocytes in a pre-dendritic state by silencing key molecular players and ensuring that unwarranted DC-driven immune responses do not occur. Monocytes are also able to display macromolecular C1 on their surface, representing a novel mechanism for the recognition of circulating “danger”. Translation of this danger signal in turn, provides the requisite “license” to trigger a differentiation pathway that leads to adaptive immune response. Based on this evidence, the second hypothesis proposes that deficiency in C1q dysregulates monocyte-to-DC differentiation and causes inefficient or defective maintenance of self-tolerance. The fact that C1q receptors (cC1qR and gC1qR) are also expressed on the surface of both monocytes and DCs, suggests that C1q/C1qR may regulate DC differentiation and function through specific cell-signaling pathways. While their primary ligand is C1q, C1qRs can also independently recognize a vast array of plasma proteins as well as pathogen-associated molecular ligands, indicating that these molecules may collaborate in antigen recognition and processing, and thus regulate DC-differentiation. This review will therefore focus on the role of C1q and C1qRs in SLE and explore the gC1qR/C1q axis as a potential target for therapy.